Pediatric Posttraumatic Cystic Bone Lesion - Zehra Filiz Karaman; Musa Onem (Galenos Publishing House, 2022)
4-year-old girl presented to emergency department with left wrist pain after trauma. Radiographs demonstrated a torus fracture of the distal radius. At the third month following the trauma, a control radiograph is obtained. In the radiograph, a radiolucent lesion close to the former torus fracture site is noticed (Figure 2). Then, CT is performed for further examination (Figure 3). CT demonstrated cortical, well-circumscribed non-expansile subcentimeter lesion.